Bouldering psychotherapy is not inferior to cognitive behavioural therapy in the group treatment of depression: A randomized controlled trial. (17th November 2021) - Luttenberger, Katharina; Karg‐Hefner, Nina; Berking, Matthias; Kind, Leona; Weiss, Maren; Kornhuber, Johannes; Dorscht, Lisa
Abstract : Objectives: Bouldering has shown promising results in the treatment of various health problems. In previous research, bouldering psychotherapy (BPT) was shown to be superior to a waitlist control group and to physical exercise with regard to reducing symptoms of depression. The primary aim of this study was to compare group BPT with group cognitive behavioural psychotherapy (CBT) to test the hypothesis that BPT would be equally as effective as CBT. Design: We conducted a randomized, controlled, assessor‐blinded non‐inferiority trial in which 156 outpatients meeting the criteria of a depressive episode according to the Diagnostic and Statistical Manual of Mental Disorders (DSM‐IV) were randomly assigned to one of the two intervention groups (CBT: N = 77, BPT: N = 79). Methods: Intervention groups were manualized and treated for 10 weeks with a maximum of 11 participants and two therapists. The primary outcome was depressive symptom severity assessed with the Montgomery–Åsberg Depression Rating Scale (MADRS) and the Patient Health questionnaire (PHQ‐9) at the beginning and end of the treatment phase as well as one year after the end of treatment. Result: In both groups, depressive symptoms improved significantly by an average of one severity level, moving from moderate to mild depressive symptoms after therapy (MADRS difference scores: BPT −8.06, 95% CI [−10.85, −5.27], p < .001; CBT −5.99, 95% CI [−8.55, −3.44], p < .001). The non‐inferiority of BPT in comparison with CBT was established on the basis of the lower bound of the 95% confidence interval falling above all of the predefined margins. BPT was found to be effective in both the short ( d = 0.89) and long term ( d = 1.15). Conclusion: Group BPT was found to be equally as effective as group CBT. Positive effects were maintained until at least 12 months after the end of therapy. Thus, BPT is a promising approach for broadening the therapeutic field of therapies for depression. Practitioner points: Physical activity is effective in the treatment of depression and current guidelines explicitly recommend it as a complementary method for the treatment of depression. Nevertheless, body‐related interventions are still underrepresented in current treatments for depression. Bouldering psychotherapy (BPT) combines physical activity with psychotherapeutic content. Its concept relies on proven effective factors from CBT such as exposure training, problem solving and practicing new functional behaviours and is thus an enrichment and implementation of CBT methods on the bouldering wall. The positive effect of group bouldering psychotherapy (BPT) in reducing depressive symptoms in outpatients with depression is not inferior to the effect of group cognitive behavioural therapy (CBT). Additionally the 10‐weeks BPT‐programme significantly improved symptoms of anxiety and interpersonal sensitivity as well as health‐related quality of life, coping, body image, self‐efficacy, and global self‐esteem.